Kreativitas Singkong Lokal untuk Kebangkitan Ekonomi Wanita Tani Desa Sambak Kabupaten Magelang - Hutajulu, Dinar Melani; Gunawan, Muhammad Iqbal Fanani; Panjawa, Jihad Lukis; Sritutur, Fera Febriana; Damayanti, Putri Nisrina; Dzakirah, Aini Fadhilah (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Sambak Village is recognized for its abundant agricultural output, particularly cassava. The local Women Farmers Group (Kelompok Wanita Tani/KWT) of Sambak Village has actively engaged in processing cassava into ready-to-consume products, which are marketed within the surrounding areas. Initially, these products were well received by consumers. However, over time, increasing competition from similar products has led to a decline in consumer interest and a subsequent decrease in income for the group. To address this challenge, a community service team proposed product diversification to enhance the competitiveness and value of cassava-based products. The solution introduced new processed products—cassava-based brownies and soft cookies—that have higher market value. The program consisted of socialization, demonstrations, and mentoring. Participants in the program consist of 20 KWT members. They received socialization on the importance of product diversification for improving household income, calculating cost of goods sold, ensuring hygiene and product safety, and applying proper packaging techniques. The demonstration phase included the preparation of both steamed and baked brownies, as well as soft cookies using cassava as the main ingredient. Mentoring sessions focused on improving packaging quality to meet consumer expectations and enhance marketability. Based on ease of preparation and participant feedback, the group decided to focus on producing baked brownies as their primary follow-up product. The training sessions were met with enthusiasm, as participants acquired new knowledge and practical skills that they were eager to implement. Their motivation was further supported by the provision of baking tools and raw materials from the community service team. This community engagement initiative is expected to have a meaningful impact on the economic empowerment of the Sambak Village KWT by increasing their capacity to produce innovative, value-added cassava products that are more competitive in the local market.